Correlation of Lipid Profile with Thyroid Stimulating Hormone in Pregnant Females (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: Pregnancy is a state which requires more metabolic fuels. Changes in the hormonal levelsin pregnancy alter lipid profile also in pregnant women. Thyroid hormone abnormality without any historyof thyroid disease may lead to alteration of triglycerides, phospholipids, total cholesterol, and variouslipoproteins levels in pregnancy which increases the risk for CVS disease.Aim: The aim of the study is to find out the association among TSH and lipid profile in pregnant females.Materials and Methods: The observational study was conducted at Biochemistry Department, SBKSMedical Institute & Research Center, Piparia, Vadodara, Gujarat, India. 100 antenatal cases from wereenrolled after taking an informed consent. 50 pregnant women were in 2nd trimester and 50 pregnant womenwere in 3rd trimester. Blood samples were drawn to estimate lipid profile and TSH. Interpretation of data wasdone using Medcalc software.Results: The mean level of TSH was 1.71(1.26) in 2nd trimester pregnant females and 2.68(0.72) in 3rdtrimester pregnant females, difference between them was statistically significant. Significant negativecorrelation was found between TSH and total cholesterol in 3rd trimester pregnancy. There was a significantpositive correlation was seen between TSH and triglyceride and between TSH and VLDL in 3rd trimester.Conclusion: Significant increase in TSH level is found in 3rd trimester pregnant females compare to 2ndtrimester pregnant females. Significant correlation is also found between TSH and lipid profile in 3rdtrimester. Regular checkups of Thyroid hormones are required in later stages of pregnancy to prevent furthercomplications.
Keywords: Lipid Profile, TSH, Pregnancy.